PENGARUH INTEREST GROUP TERHADAP KEBIJAKAN BRITANIA RAYA TERKAIT BREXIT - Febrian, Koko Catra; Oktariani, Farah Wahyu; Agus, Rahmat Reski; Pertiwi, Rahmatya Nur Wibi (Global and Policy Journal of International Relations, 2018)
ABSTRACTIn a democratic country, like the United Kingdom, has a political party that supports and rejects foreign policy. Competition of political parties in the United Kingdom forced the public to express their aspirations regarding the BREXIT policy. The pro-party against such conservative and conservative referendums like the workers' party makes two camps in Great Britain. Pro's against the referendum is called VOTE LEAVE and the camp is called VOTE REMAIN. The presence of both camps and interest groups has forced the Great Britain to be forced to exercise their right to vote again. The public is demanded in a condition of choosing that Great Britain out or remain a member of the European Union. In accordance with the final result of the referendum, the VOTE LEAVE stronghold won the most votes, the United Kingdom de jure out of the European Union. Along with the incident, David Cameron resigned and was replaced by Theresa May. Theresa May signed Article 50 as a legality that the United Kingdom was out of EU membership.Keywords: Brexit, Vote Leave, Vote Remain, domestic politicsDOI: https://doi.org/10.33005/jgp.v6i01.1839